Konkurencja między funkcjami podatkowymi - Nowak, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The author pays special attention to unprofitable goals of tax instituting and its greater role in this process. Social and economic functions of taxation are very important in construction of economic environment. However, the article exhibits tax financial function as a fundamental premise to build rational and effective tax system. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 258-268